Detecting Malicious Packet Losses - SHANKER REDDY D, ANIL KUMAR D M, RANITA PAUL CHOWDHURY (2009)
INNTERNAL Guide : Supriya Kamthania EXTERNAL Guide: Nagendran Scientist S USN No : 1MJ07CS408, 1MJ06CS081, 1MJ07CS401 and 1MJ07CS407 Carried out at : NATIONAL Aerospace Laboratories Bangalore-560017 Acc No : PR1718 Project Report CD No : RC76
Keywords: Detecting Malicious